A guilty satisfaction: detective fiction and the reader - Pendrill, Michael Laurie (2012)
The purpose of this thesis is to explore the reasons why readers choose to read detective fiction. Taking Thomas De Quincey’s satirical identification of the aesthetic quality of murder, I look at Edgar Allan Poe’s detective fiction to find a non-satiric version of the same argument that emphasises the balancing quality of the ethical to the aesthetic. W.H. Auden’s essay “The Guilty Vicarage” offers an argument concerning the reader’s position in relation to these opposite components. I explore the ways in which Auden’s arguments build into Freud’s understanding of guilt, daydreams, the moral conscience, jokes, the uncanny and the death drive, and how these can be applied to the genre to help illustrate the reader’s experience. Concurrent to this I offer an analysis of how the parallel developments in literary theory, particularly those of Barthes and Shklovsky, can be incorporated to enrich the understanding of these Freudian positions within the modern reader’s experience. It is my intention to open up a field of study within the genre that differs from the traditional Marxist approach. Particular emphasis is placed on the role of the experience of pleasure found when moments of commonality between the aesthetic and the ethical are reached– how these are often unsatisfactory– necessitating a repetition of the literary experience. It is my argument that such an approach to the reader’s position within the genre has not been explored in such a detailed fashion, centring as it does upon the active role of guilt in pleasure felt by the reader as the motivation to repeat. To illustrate that this is an argument that is applicable to different historical phases of detective fiction the study undertakes analysis of the following authors: Arthur Conan Doyle, Wilkie Collins, Agatha Christie, Raymond Chandler, Graham Greene and John Fowles